2021
DOI: 10.1002/hep.32045
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Synthase–Suppressor Screening Identifies Sorting Nexin 8 as a Therapeutic Target for NAFLD

Abstract: BaCKgRoUND aND aIMS: NAFLD is the most prevalent chronic liver disease without any Food and Drug Administration-approved pharmacological intervention in clinic. Fatty acid synthase (FASN) is one of the most attractive targets for NAFLD treatment because of its robust rate-limiting capacity to control hepatic de novo lipogenesis. However, the regulatory mechanisms of FASN in NAFLD and potential therapeutic strategies targeting FASN remain largely unknown. MetHoDS aND ReSUltS:Through a systematic interactomics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 50 publications
0
32
0
3
Order By: Relevance
“…Interestingly, diverse lncRNAs that target genes related to NAFLD were identified in our study. NAFLD is caused by a build-up of fat in the liver and mainly occurs in people who are overweight or obese [47]. The target genes of the lncRNAs are mainly enriched in the Oxidative phosphorylation, EGFR tyrosine kinase inhibitor resistance and MAPK signaling pathway, which is related to diverse functions such as energy metabolism and adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, diverse lncRNAs that target genes related to NAFLD were identified in our study. NAFLD is caused by a build-up of fat in the liver and mainly occurs in people who are overweight or obese [47]. The target genes of the lncRNAs are mainly enriched in the Oxidative phosphorylation, EGFR tyrosine kinase inhibitor resistance and MAPK signaling pathway, which is related to diverse functions such as energy metabolism and adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effective dose of PTM needs to be further explored. Alternatively, manipulating the regulatory pathway of FASN under pathological conditions is a promising method for the treatment of NAFLD, such as the recent identified FASN-binding sorting nexin 8 [ 34 , 36 ]. The direct inhibition of FASN might trigger chronic on-target safety risks due to the reduced β -oxidation of fatty acids by compromising the activity of PPARα, since FASKOL mice showed lipid accumulation and hypoglycemia with a zero-fat diet or fasting.…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid synthase catalyzes hepatic DNL and is a key enzyme regulating hepatic lipid metabolism [119]. Studies have demonstrated that FASN expression is significantly elevated in the liver of NAFLD or obesity [120,121].…”
Section: Fatty Acid Synthase Inhibitorsmentioning
confidence: 99%
“…Studies have demonstrated that FASN expression is significantly elevated in the liver of NAFLD or obesity [120,121]. Inhibition of FASN improved hepatic steatosis by inhibiting hepatic fatty acid synthesis [119,122,123]. TVB-2640 is a reversible FASN inhibitor that has been shown to reduce hepatic DNL and hepatic TG levels in subjects in a small clinical study.…”
Section: Fatty Acid Synthase Inhibitorsmentioning
confidence: 99%